Sox9 Determines Translational Capacity During Early Chondrogenic Differentiation of ATDC5 Cells by Regulating Expression of Ribosome Biogenesis Factors and Ribosomal Proteins - Caron, Marjolein M. J.; Eveque, Maxime; Cillero-Pastor, Berta; Heeren, Ron M. A.; Housmans, Bas; Derks, Kasper; Cremers, Andy; Peffers, Mandy J.; van Rhijn, Lodewijk W.; van den Akker, Guus; Welting, Tim J. M. (Frontiers in Cell and Developmental Biology, 2021)
Introduction: In addition to the well-known cartilage extracellular matrix-related expression of Sox9, we demonstrated that chondrogenic differentiation of progenitor cells is driven by a sharply defined bi-phasic expression of Sox9: an immediate early and a late (extracellular matrix associated) phase expression. In this study we aimed to determine what biological processes are driven by Sox9 during this early phase of chondrogenic differentiation. Materials: Sox9 expression in ATDC5 cells was knocked-down by siRNA transfection at the day before chondrogenic differentiation or at day 6 of differentiation. Samples were harvested at 2 hours, and 7 days of differentiation. The transcriptomes (RNA-seq approach) and proteomes (Label-free proteomics approach) were compared using pathway and network analyses. Total protein translational capacity was evaluated with the SuNSET assay, active ribosomes with polysome profiling and ribosome modus with bicistronic reporter assays. Results: Early Sox9 knockdown severely inhibited chondrogenic differentiation weeks later. Sox9 expression during the immediate early phase of ATDC5 chondrogenic differentiation regulated the expression of ribosome biogenesis factors and ribosomal protein subunits. This was accompanied by decreased translational capacity following Sox9 knockdown, and this correlated to lower amounts of active mono- and polysomes. Moreover, cap- versus IRES-mediated translation was altered by Sox9 knockdown. Sox9 overexpression was able to induce reciprocal effects to the Sox9 knockdown. Conclusion: Here we identified an essential new function for Sox9 during early chondrogenic differentiation. A role for Sox9 in regulation of ribosome amount, activity and/or composition may be crucial in preparation for the demanding proliferative phase and subsequent cartilage extracellular matrix-production of chondroprogenitors in the growth plate in vivo.